Penanaman Kecerdasan Spiritual Peserta didik di Sekolah Dasar Islam Kabupaten Brebes - Muh Luqman Arifin (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The purposes of this study were to describe the efforts of schools in instilling Spiritual Intelligence (SI) into students and to determine the level of students’ SI in Islamic Primary Schools (IPS). This study used a descriptive qualitative-quantitative method resting upon a phenomenological approach with data collection techniques using interviews and observations to teachers and students, as well as the SI statement questionnaire. The research was carried out at Takhasus Al-Qur’an Elementary School (SDTQ), Harapan Umat Integrated Islamic School (SDITHU), and Al-Ambary Integrated Islamic Elementary School (SDITA) located in Brebes Regency, Indonesia. The data were analyzed at 5 intervals according to Saifuddin Azwar in a quantitative form. The results showed that the processes of instilling SI in SDI were carried out by establishing a vision and mission with Islamic tagline, the implementation in curricular and extracurricular activities, and exemplaryness by the teachers. The average levels of SI in the three schools for the three categories of honesty, respect for parents and teachers, and respect for others lied in decending orders from SDTQ Al-Ikhlas, SDIT Harapan, to SDIT Al-Ambari. In addition, the study revealed the results that the SI predicate was “Very Good” for female students and “Good” for male students.